A RARE CASE OF THE POSTERIOR INFERIOR CEREBELLAR ARTERY - (:unkn) unknown (KARGER, 1995)
posterior inferior cerebellar artery (PICA) is normally a branch of the vertebral artery. In this rare case, the unilateral left vertebral artery continued its course as the left PICA, and an extremely small caliber left vertebral artery joined the right vertebral artery to form the basilar artery. This rare feature of the PICA is demonstrated and its relation to neighboring structures is discussed. Also, the literature concerning the PICA is reviewed.
Keywords: POSTERIOR INFERIOR CEREBELLAR ARTERY; VERTEBRAL ARTERY; SURGICAL ANATOMY